Assessment of Vegetation Habitat Types and Characteristics of Potential Nesting Trees for White‐Backed Vultures (Gyps africanus) in Kempiana and Manyeleti Nature Reserves, Mpumalanga Province, South Africa - Fidèle Ezéchiel K. Hounnouvi; Stanislas Mahussi Gandaho; Fern Bain; Peter Hamming; Lindy J. Thompson (Ecology and Evolution)
ABSTRACT The White‐backed Vulture (Gyps africanus) is widespread in sub‐Saharan Africa but faces population decline due to habitat degradation, poisoning, food loss, and energy infrastructure. This study examines how tree species, height, trunk circumference, and vegetation type influence nest placement in the Kempiana and Manyeleti Nature Reserves, South Africa. Using high‐resolution aerial imagery, we identified habitat types and surveyed 106 trees, including 31 nesting trees. Data collection spanned 3 weeks (12.02.2024–01.03.2024) during the non‐breeding season, with fieldwork conducted 5 days per week (6 h/day). A four‐ six‐member team recorded geomorphological variables via GIS and tree characteristics. The thinning vegetation in autumn enhanced nest visibility. Nesting trees were found across four vegetation types: 67% in mixed woodland with grass, 20% in wooded savanna, 10% in savanna grassland, and 3% in bare soil/built areas. Fischer's exact test and Dunn's test indicated that nesting trees were significantly selected based on height, trunk circumference, and proximity to rivers and roads. Nesting trees had a median height of 14.5 m, a CBH of 2.12 m, and were located a median distance of 2.23 km from rivers and 5.65 km from roads. Our findings confirm that White‐backed Vultures prefer large trees near rivers but away from roads for nesting. We recommend future research on habitat degradation, particularly the loss of large riparian trees, and its impact on nesting site availability. Conservation efforts should focus on preserving large trees and reducing anthropogenic disturbances in critical nesting areas.